2016
DOI: 10.3389/fendo.2016.00161
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Elevated Thyroid-Stimulating Hormone at Birth and Parent-Reported Problem Behavior at Preschool Age

Abstract: ObjectivesMild level of iodine deficiency during pregnancy may reduce maternal thyroid hormone production and supply to the fetus hence affecting brain neurodevelopment. The aim of the present study was to investigate the association between elevated neonatal thyroid-stimulating hormone (TSH) level (>5 mU/L), used as a marker of maternal mild iodine deficiency during late pregnancy, and behavioral development of preschool children.MethodsThis retrospective cohort study included 310 Belgian mothers and their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…The Belgian study conducted by Trumpff et al . found no association between TSH concentration (0.1–15 U/L) and cognitive, psychomotor and behavioral development at preschool age when adjusting for confounding factors using multivariate analysis (28, 29, 56). Cognitive and psychomotor assessment was performed by psychologists using age-appropriate clinical diagnostic tools, respectively, the Wechsler Preschool and Primary Scale of Intelligence (third edition) and Charlop-Atwell Scale of Motor Coordination (28, 30).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The Belgian study conducted by Trumpff et al . found no association between TSH concentration (0.1–15 U/L) and cognitive, psychomotor and behavioral development at preschool age when adjusting for confounding factors using multivariate analysis (28, 29, 56). Cognitive and psychomotor assessment was performed by psychologists using age-appropriate clinical diagnostic tools, respectively, the Wechsler Preschool and Primary Scale of Intelligence (third edition) and Charlop-Atwell Scale of Motor Coordination (28, 30).…”
Section: Discussionmentioning
confidence: 91%
“…Cognitive and psychomotor assessment was performed by psychologists using age-appropriate clinical diagnostic tools, respectively, the Wechsler Preschool and Primary Scale of Intelligence (third edition) and Charlop-Atwell Scale of Motor Coordination (28, 30). Psychosocial development was assessed using the Child Behavior Check List for age 1½–5 years standardized and validated questionnaire completed by the mothers, a widely used measure for evaluating maladaptive behavioral and emotional problems (56). Of note, the sample size had the statistical power to detect an IQ score difference as small as 4.3 points.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the five studies of neonatal thyroid hormones and ADHD symptoms were cohort studies (Table 6): Trumpff et al (2016) studied a Belgian cohort ( N total =310), 63 and there were two studies of Canadian cohorts with less than 100 participants each (Ishaik et al 2000; Simic et al 2009). 15,64 Two of the five studies had matched case–control designs: 65,66 ADHD cases (identified through neurodevelopmental diagnostic clinics in Washington, D.C) were matched on the day of newborn screening and birth hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies have attempted to address this question. A series of studies in Belgian children that assessed the relationship between newborn screening TSH concentrations and various neurodevelopmental outcomes found no relationship between mild TSH elevation (up to 15 mIU/L) and cognitive or psychomotor development or parent-reported behavior scores at 4–6 years of age [ 54 – 56 ]. However, the power of these studies to detect differences in outcomes was limited by the small number of patients with elevated TSH concentrations, particularly in the 10–15 mIU/L range.…”
Section: Introductionmentioning
confidence: 99%